Czarno-biały plakat filmowy w okresie PRL-u – estetyka i ekspresja. Autonomizacja wypowiedzi artystycznej a funkcja plakatu filmowego - Kulpińska, Katarzyna (Załącznik Kulturoznawczy, 2024)
This article refers to a specific group among Polish film posters created in the 1950s–70s. They are based on black-andwhite colors advertising films of various genres, representing European, Asian and American cinema. The use of the most radical contrast between black and white, occasionally broken up with a counterpoint of red, is characteristic of the geometric-structural and typographic trend, although the creators of colorful painting posters also created expressive black and white film posters. Given the attachment of several artists to black-and-white solutions, it is reasonable to ask whether that peculiar self-restraint in color was an exercise in discipline or, on the contrary, a test of creativity, or perhaps it was but a result of mundane printing problems and was dictated by concerns over print quality. The analysis of the works (from a technical and aesthetic point of view, taking into account the color theory, Gestalt theory, the nōtan concept) is accompanied by a reflection on the freedom and degree of autonomy of authorial expression in the cultural poster in relation to its primary functions. The article thus constitutes an attempt to answer the question whether every film poster can be treated as an intersemiotic message or, following Jan Lenica’s train of thought: “A poster is indeed, first and foremost, an aesthetic message” and its creator prefers the artistic concept (in this case based on black-andwhite) over the possibility to refer to the movie plot itself.